Peredam Konflik Agama: Studi Analisis Penyelesaian di Tolikara Papua 2015 - MOH ROSYID (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2017)
This paper aims at understanding the importance of early warning system on interreligious conflict, so that similar case such as the fire incident of Al-Muttaqin Mosque in Karubaga, Tolikara, Papua on Friday Syawal 1st 1436 H/July 17th 2015. Fire occurred when Muslim performing Ied Fitri prayer in an open space. The case seemed to be a climax of previous events: 1) Gereja Injili di Indonesia (GIDI/ Indonesian Evangelical Church) held an international seminar involving people from all over the world, on the day of Ied Fitri. Moreover, GIDI released a notice banning Muslim from performing Ied Prayer, 2) the committee of KKR some-how felt irritated with Muslims’ activity during Ied celebration since early in the morning, 3) state apparatus were not prepared for the conflict. Early warning system needs to be developed to prevent such conflict re-occur in this country. The cause of conflict should be settled such as based on the finding of the Fact Finding Team of the Muslims Committee for Tolikara (Komat): the criminals should be brought to the court; the notice released by GIDI should be evaluated; Interreligious forum (FKUB) should be balanced between all religious beliefs; local regulation on the banning of building a place of worship other than GIDI’s church must be evaluated.